Making Red Books: The Popular Collections of the Mexican Left (1934–1940) - Rivera Mir, Sebastián (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2021)
This article analyzes the mechanisms and methods that some Mexican leftist publishers used to build a market for their publications during the presidency of Lázaro Cárdenas (1934–1940). These publishers believed that the strategy of creating popular collections would allow them to acquire new readers, expand their catalogues, and professionalize the field of publishing. Following Roger Chartier, this paper reconstructs a part of Mexican publishing history that has seldom been addressed. I argue that the efforts of leftist publishers in this period explain the preponderance of Marxism in the Mexican publishing industry for most of the twentieth century.